Russia’s State Policy on the Development of Science at Universities: Lessons from the 90s - I. G. Dezhina (Высшее образование в России, 2023)
The article discusses the influence of state programs on research development in Russian universities in the first post-Soviet decade. After the USSR collapse the conditions for doing research in Russia worsened significantly due to a sharp reduction in budget funding with unessential other sources of support. Research conducted in higher education institutions was a small fraction of the entire system, and involvement in science was not among the primary activities of universities, except for a small number of leading universities. At the same time, mostly higher education institutions were responsible for training of highly qualified personnel. This discrepancy posed a threat for the science system. At the state level, a number of separate targeted programs was initiated, with an emphasis on fundamental research in universities. The aim of the article is to identify and systematize, in the framework of these state programs, the main factors affected the development of science in higher education institutions. The research methods include literature review, analysis of statistical data, and interpretations of surveys conducted in the 90s. It is shown that the programs’ results were modest and did not change the scale of university science in the country. The hampering factors were associated with regulatory and legal restrictions, sub-optimal choice of areas for support, underfunding and dispersion of financial support, and insufficient consideration of the former research specialization of universities. At the same time, these programs gave impetus to the discussion of the concepts of research universities, which later were implemented.